Implementation of Bismuth Chalcogenides as an Efficient Anode: A Journey from Conventional Liquid Electrolyte to an All-Solid-State Li-Ion Battery - Rini Singh; Pooja Kumari; Manoj Kumar; Takayuki Ichikawa; Ankur Jain (Molecules, 2020)
Bismuth chalcogenide (Bi2X3; X = sulfur (S), selenium (Se), and tellurium (Te)) materials are considered as promising materials for diverse applications due to their unique properties. Their narrow bandgap, good thermal conductivity, and environmental friendliness make them suitable candidates for thermoelectric applications, photodetector, sensors along with a wide array of energy storage applications. More specifically, their unique layered structure allows them to intercalate Li+ ions and further provide conducting channels for transport. This property makes these suitable anodes for Li-ion batteries. However, low conductivity and high-volume expansion cause the poor electrochemical cyclability, thus creating a bottleneck to the implementation of these for practical use. Tremendous endeavors have been devoted towards the enhancement of cyclability of these materials, including nanostructuring and the incorporation of a carbon framework matrix to immobilize the nanostructures to prevent agglomeration. Apart from all these techniques to improve the anode properties of Bi2X3 materials, a step towards all-solid-state lithium-ion batteries using Bi2X3-based anodes has also been proven as a key approach for next-generation batteries. This review article highlights the main issues and recent advances associated with Bi2X3 anodes using both solid and liquid electrolytes.